K.H AHMAD DAHLAN TINJAUAN TERHADAP KONSEP PENDIDIKANNYA - SUGIATI SUGIATI (CENDEKIA: Jurnal Ilmu Pengetahuan, 2022)
Ahmad Dahlan is a figure in the religious reform movement in Indonesia, both in the socio-cultural, political, educational fields, as well as a national hero in the effort to pioneer the independence of the Republic of Indonesia. Efforts in reforming the field of education, he formulated an educational concept that integrates the education system of Islamic boarding schools with a modern education system that is in accordance with the demands of the times. KH. Ahmad Dahlan changed his education system, which originally consisted of dualism of education, into an education system that no longer differentiated between religious education and general education. KH. Ahmad Dahlan aspires to the formation of a generation of "intellectual Ulama, and intellectual Ulama". In formulating the concept of education, KH. Ahmad Dahlan combines faith, knowledge and charity. Because according to him, education does not only transfer knowledge, but also A. Dahlan applies education to his students, there is a balance between knowledge and charity which is imprinted in each individual and his students. In this case, A. Dahlan believes that Muslims can advance in various sciences only by returning to the Qur'an and Al-Hadith as a reference in the system of life and life. The concept of education formulated by A. Dahlan is an Islamic concept which of course is based on the Qur'an and Al-Hadith. To obtain supporting data in this study, the authors use the documentation method, namely through library research (liberary search) by collecting or taking an inventory of books, newspapers, notes, magazines, agendas, leggers, and others related to the problem. . Furthermore, as a conclusion in this study that between the concept of education according to KH. Ahmad Dahlan with the concept of Islamic education is very relevant, both of which have the same basis and purpose for the formation of a Muslim personality and both lead to the unification of the Islamic education system. ABSTRAKAhmad Dahlan adalah seorang tokoh gerakan pembaharuan keagamaan di Indonesia baik dalam bidang sosial budaya, politik, pendidikan, juga sebagai pahlawan Nasional dalam upaya merintis kemerdekaan RI. Upaya dalam pembaharuan dibidang pendidikannya, ia merumuskan suatu konsep pendidikan yang mengintegrasikan antara sistem pendidikan pondok pesantren dengan sistem pendidikan modern yang sesuai dengan tuntutan zaman. KH. Ahmad Dahlan merubah sistem pendidikannya yang semula terdiri dualisme pendidikan menjadi sistem pendidikan yang tidak lagi memilah-milah antara pendidikan agama dengan pendidikan umum. KH. Ahmad Dahlan mencita-citakan terbentuknya generasi yang “intelektual Ulama, dan Ulama yang Intelektual”. Dalam merumuskan konsep pendidikannya, KH. Ahmad Dahlan memadukan antara iman, ilmu dan amal. Karena menurutnya bahwa dalam pendidikan tidak saja hanya mengalihkan ilmu pengetahuan, tetapi juga A. Dahlan menerapkan pendidikan kepada para muridnya adanya keseimbangan antara ilmu dan amal yang terpatri dalam setiap pribadi dan anak didiknya. Dalam hal ini A. Dahlan berkeyakinan bahwa umat islam bisa maju dalam berbagai ilmu pengetahuan hanya dengan kembali kepada Al-Qur’an dan Al-Hadits sebagai rujukan didalam sistem hidup dan kehidupan. Konsep pendidikan yang dirumuskan A. Dahlan adalah konsep islam yang tentu saja berdasarkan Al-Qur’an dan Al-Hadits. Untuk memproleh data yang menunjang dalam penelitian ini, penulis menggunakan metode dokumentasi, yaitu melalui penelitian kepustakaan (liberary search) dengan cara mengumpulkan atau menginventarisasi buku-buku, surat kabar, catatan, majalah, agenda, legger, dan lain-lainnya yang berhubungan dengan masalah. Selanjutnya sebagai kesimpulan dalam penelitian ini bahwa antara konsep pendidikan menurut KH. Ahmad Dahlan dengan konsep pendidikan Islam sangat relevan sekali, dimana keduanya mempunyai dasar dan tujuan yang sama terbentuknya kepribadian muslim dan sama-sama menuju kepada penyatuan sistem pendidikan Islam.